(untitled) - Kenneth K S. Ch'en (Princeton, New Jersey, 1973)
The book details the history of buddhism in China, from its introduction in Han Dynasty through the period of its most creative maturity in the T'ang Dynasty, its later decline and survival to the present
Keywords: buddhism - china - history